Arbuscular mycorrhizal fungi and Trichoderma harzianum alter salicylic acid–jasmonic acid balance to suppress Fusarium wilt in tomato - Zhang, Kangxu; Wang, Haixi; Xie, Wei; Niu, Tianyi; Fu, Wei; Zhang, Xin; Hao, Zhipeng; Chen, Baodong (Frontiers in Plant Science, 2025)
Fusarium wilt, caused by Fusarium oxysporum, poses a significant challenge to tomato production, and sustainable control strategies are urgently needed. Beneficial microbes such as arbuscular mycorrhizal (AM) fungi and Trichoderma harzianum are widely applied as biocontrol agents, but their combined effects and the underlying immune mechanisms in host plants remain insufficiently understood. In this study, greenhouse experiments were conducted to evaluate the impacts of inoculation with Rhizophagus irregularis and T. harzianum, individually and together, on pathogen colonization, nutrient uptake, hormone signaling, and defense responses in tomato. Quantitative PCR revealed that both beneficial fungi significantly reduced F. oxysporum colonization in roots, yet co-inoculation did not provide additional suppression compared with single inoculations. Hormonal profiling showed that pathogen infection alone activated jasmonic acid (JA)-dominated defenses, whereas inoculation with either AM fungi or T. harzianum redirected immunity toward a salicylic acid (SA)-associated state. This shift was characterized by elevated SA accumulation, increased activity of phenylalanine ammonia-lyase (PAL) and polyphenol oxidase (PPO), and reduced levels of JA and its derivatives. Dual inoculation reproduced these hormonal and enzymatic changes but did not further enhance them. Correlation analysis revealed that SA enrichment and PAL/PPO activities were negatively associated with pathogen abundance, whereas JA-related compounds correlated positively with disease severity. These findings suggest that beneficial fungi mitigate Fusarium wilt by reprogramming host immune responses from JA- to SA-dominated pathways, but their combined application does not produce additive benefits. This work provides new insights into the hormonal trade-offs underlying microbe-induced resistance and informs the design of microbial consortia for sustainable plant disease management.